1985
DOI: 10.1007/bf00291649
|View full text |Cite
|
Sign up to set email alerts
|

On the significance of true trisomy 20 mosaicism in amniotic fluid culture

Abstract: Nine new cases of prenatally detected true mosaic trisomy 20 (T20) are reported. In three instances the fetuses were aborted. One fetus showed multiple malformations associated with a high percentage of T20 cells among amniotic fluid (AF) cells and fibroblasts of different fetal tissues. In two other fetuses only a slight facial dysmorphy was seen which was accompanied by a low percentage of T20 cells among AF cells. In five instances the pregnancies were carried to term, and normal somatic and psychomotor dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…A few reports were found that describe severely affected individuals, primarily fetuses or those that suffered neonatal death from lethal malformations. While they do share some of the features listed above, their differences lie in the additional anomalies noted that we have not included in our phenotype [Pallister et al, 1976;Pan et al, 1976;Djalali et al, 1985;Hsieh et al, 1992]. There is little consistency in phenotype among these cases, as they are described.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…A few reports were found that describe severely affected individuals, primarily fetuses or those that suffered neonatal death from lethal malformations. While they do share some of the features listed above, their differences lie in the additional anomalies noted that we have not included in our phenotype [Pallister et al, 1976;Pan et al, 1976;Djalali et al, 1985;Hsieh et al, 1992]. There is little consistency in phenotype among these cases, as they are described.…”
Section: Resultsmentioning
confidence: 55%
“…However, most of the cases in these studies had short follow-up times and much of the data is based on birth records. In some studies there is a trend increasing percent of trisomic cells detected prenatally, and risk of abnormal outcome; however, this relationship is not consistent enough to be useful in prenatal counseling [Djalali et al, 1985;Reish et al, 1998;Wallerstein et al, 2000;Robinson et al, 2005]. No pattern of malformation has been described in the literature.…”
Section: Introductionmentioning
confidence: 86%
“…This abnormal chromosome, while it can be identified prenatally in amniotic fluid, is postnatally identified almost exclusively in cultured fibroblasts and is rarely observed in peripheral blood. Djalali et al (1985) have proposed that a relationship may exist between the risk of phenotypic abnormalities and the percentage of trisomy 20 cells identified in amniotic fluid cultures and have suggested that it may be possible to stratify patients into 'high-risk' and 'low-risk' categories based on the likely mechanism generating the trisomy. More recently, Hsu et al (1991) have re-examined the data on mosaic trisomy 20 and concluded that no relationship exists between the percentage of trisomy 20 cells and the frequency of an abnormal phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…1,5 It has been suggested that the percentage of trisomic cells in the culture or the presence of trisomic cells in foetal tissues may predict a poor outcome. 5,6 The literature, however, suggests that neither of these indicators is reliable. We aimed to identify cases of mosaic trisomy 20 found on amniocentesis or chorionic villus sampling (CVS) in New Zealand in the last 10 years to provide a representative review of the clinical features and outcomes associated with this finding.…”
Section: Introductionmentioning
confidence: 94%